Response of the American equatorial ionization anomaly to 2016 Arctic sudden stratospheric warming events - Idolor, O. R.; Akala, A. O.; Bolaji, O. S.; Oyeyemi, E. O.; Agbele, A. T. (Frontiers in Astronomy and Space Sciences, 2022)
Aside the rapid ionospheric response to geomagnetic forcing originating from the Sun during extreme space weather events, forcing from the lower atmosphere below still exert a significant influence on the ionosphere during quiet time conditions. This study examines the ionospheric response of the equatorial ionization anomaly (EIA) in the American sector to the combined influence of the cascades of Sudden Stratospheric Warming (SSW) events and the geomagnetic storms that coexisted with them during the period of January-March, 2016. We adopted a multi-instrument and multi-modeling approach with the study locations spanning ±40° geomagnetic latitudes. Our results showed a hemispheric asymmetric in the total electron content (TEC) and change in total electron content (ΔTEC) distribution with higher enhancement clearly visible in the Northern Hemisphere (NH) in comparison to the Southern Hemisphere (NH). Semidiurnal signatures were observed in both ΔTEC and equatorial electrojets (EEJ) parameters for some days. The double peak zonal mean zonal wind amplitude days supported the formation of the reverse fountain effects. The different SSW peak temperature days also showed either positive or negative ionospheric response. Generally, orientation of the prompt penetration electric field (PPEF) and their strengths at either daytime or night time played a weak role in the ionosphere response during some of the geomagnetic storms. The negative and positive ionospheric response during geomagnetic storm conditions were ascribed to changes in the composition of the thermosphere, prompt penetration electric field (PPEF) and traveling atmospheric disturbances (TADs).